2020
DOI: 10.5152/j.aott.2020.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of high tibial osteotomy with combined fixator-assisted nailing and subtubercle tibial osteotomy

Abstract: The role of the platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio in the prediction of length and cost of hospital stay in patients with infected diabetic foot ulcers: A retrospective comparative study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They found that the height of the patella (CDI) in 72 knees did not change significantly after the operation and that the patellofemoral relationship was normal. Next, Bayam et al [ 8 ] combined STO with the fixator-assisted nailing technique to perform orthopedic procedures on 32 knee joints, and the study confirmed that the patellar height was not affected during at least 30 months of follow-up. In a large number of clinical studies, it has been confirmed that whether the osteotomy line passes through the tibial tuberosity is one of the evaluation criteria for the change in patellar height, and subtubercle osteotomy can effectively avoid this [ 3 – 5 , 7 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…They found that the height of the patella (CDI) in 72 knees did not change significantly after the operation and that the patellofemoral relationship was normal. Next, Bayam et al [ 8 ] combined STO with the fixator-assisted nailing technique to perform orthopedic procedures on 32 knee joints, and the study confirmed that the patellar height was not affected during at least 30 months of follow-up. In a large number of clinical studies, it has been confirmed that whether the osteotomy line passes through the tibial tuberosity is one of the evaluation criteria for the change in patellar height, and subtubercle osteotomy can effectively avoid this [ 3 – 5 , 7 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…Medial opening wedge HTO is indicated for medial compartment knee osteoarthritis with varus deformity [ 29 , 30 ]. By adjusting the femorotibial angle, the weight bearing of the knee can be redistributed [ 14 , 15 ]. Although no consensus has been reached in terms of the optimal alignment in medial opening wedge HTO, 8–10° vulgus of the post-operative anatomical femorotibial angle was often suggested [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various HTO techniques, medial opening wedge HTO, lateral opening wedge HTO, medial closing wedge HTO, and lateral closing wedge HTO are the most common subtypes [ 13 ]. For medial compartment knee osteoarthritis with varus deformity, medial opening wedge HTO alleviates the symptoms by correcting the malalignment and redistributing the body weight loading [ 14 , 15 ]. However, HTO alone does not aim to repair the structural damage of the knee.…”
Section: Introductionmentioning
confidence: 99%